Intense Exercise Increases Protein Oxidation in Spleen and Liver of Mice. (January 2014) - Kobayashi, Yukiko; Nakatsuji, Aki; Aoi, Wataru; Wada, Sayori; Kuwahata, Masashi; Kido, Yasuhiro
Studies have indicated that sports anemia is mainly associated with intravascular hemolysis induced by exercise. We hypothesized that such exercise-induced hemolysis leads to oxidative damage due to an increase in free iron caused by hematocyte destruction. Thirty-one male ICR mice were randomly divided into 3 groups: a rested control group, an intense-exercise group, and a group rested for 24 hours after intense exercise. The serum haptoglobin level of the intense-exercise group decreased compared with that of the rested control group, suggesting hemolysis. Tissue iron and protein carbonyl levels in the liver were increased after exercise, and the protein carbonyl level in the spleen on the day after exercise was significantly increased compared with that of the resting state. These results suggest that the spleen and liver, where extravascular hemolysis occurs, were subjected to oxidative modification by the free iron, which was released from large numbers of hemocytes that were destroyed due to the intense exercise.